PERAN DAN KEDUDUKAN ILMU MATEMATIKA DALAM PENDIDIKAN PANCASILA - Rambe, Yuli Nirmaida (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
This essay examines the relationship between mathematics and Pancasila Education in shaping students' character based on the nation's noble values. As a branch of science that emphasizes logic, precision, and consistency, mathematics is not only important academically but also plays a significant role in internalizing Pancasila values ​​such as justice, humanity, and wisdom. Pancasila Education aims to instill morality and national identity, which can be strengthened through a mathematical approach to decision-making and problem-solving. By integrating mathematics learning into the Pancasila values ​​framework, education becomes a strategic tool in developing rational, ethical, and responsible individuals